Rectal Perforation by a Balloon Spacer: A Rare Cause of Rectal Perforation Addressed Endoscopically - Barros,Sónia (2021)
Abstract: Prostate cancer is the second most frequent cancer in men worldwide. Dose escalation is currently the standard of care for the treatment of prostate cancer with radiation therapy. However, the rectum tends to be the dose-limiting structure when treating prostate cancer, given its proximity. The injection of biodegradable spacers between the prostate and the rectum may optimize radiotherapy treatment delivery for patients with localized disease. Nevertheless, although the overall complication rate of spacers is marginal, the benefits of spacer technologies need to be evaluated against the complication risks such as rectum perforation/necrosis. We report a case of a 59-year-old man with a diagnosis of prostate adenocarcinoma for whom hormonal treatment followed by intensity modulated radiation therapy (IMRT) was proposed. A biodegradable and expandable balloon (BioProtect®) was injected into the perirectal space without detectable immediate complications. One month later, the patient presented with a 3-day persistent rectal bleeding. The investigation confirmed a rectal perforation by the balloon spacer system.